Alpha-glucosidase and Alpha-amylase Inhibition Activity of Avocado Fruit of Nepalese Origin - Dhakal, Kamal; Shrestha, Dipesh; Pokhrel, Tamlal; Bhandari, Devi P.; Adhikari, Achyut (Current Enzyme Inhibition, 2022)
Background: Diabetes has become a major health problem due to its high prevalence, morbidity, and mortality rate. Reducing postprandial hyperglycemia has become the main target in the treatment of diabetes mellitus. So, developing new drugs with fewer side effects has been a major priority. Objective: The main objective of this study is to investigate total phenolic and flavonoid content, antioxidant activity, α-glucosidase, and α-amylase inhibition activity of Persea Americana Mill (avocado) pulp and seed. Methods: The α-glucosidase and α-amylase inhibition activity were performed using substrates PNPG and CNPG3, respectively. DPPH free radical scavenging assay was used to perform the antioxidant activity. The total phenolic content was estimated using folin-ciocalu’s reagent. Likewise, the aluminium trichloride method was applied to find out the total flavonoid content. Results: The crude methanolic extract of avocado seed revealed potent α-glucosidase inhibition activity with an IC50 1.959±0.93μg/mL followed by the avocado pulp 308±2.36μg/mL. Similarly, the IC50 for the α-amylase inhibition activity of avocado seed was found to be 120.3±1.382μg/mL. In addition, the avocado pulp and seed revealed a significant antioxidant activity with IC50 values of 75.01±0.72μg/mL and 6.445±0.62μg/mL, respectively, compared to the standard quercetin 1.525±0.5μg/mL. The total phenolic content of avocado pulp and the seed was reported as 7.031±2.87 mg of GAE/g, and 142.96±1.589 mg of GAE/g, respectively. Similarly, the total flavonoid content of avocado pulp and the seed was found to be 6.313±1.301 mg of QE/g and 48.696±0.110 mg of GAE/g, respectively. Conclusion: The avocado seed of Nepali origin was found to inhibit the digestive enzyme significantly. These findings indicate that avocado fruit of Nepali origin has the potential to develop as an alternative food therapy for diabetic patients. Further research is required to find out the inhibitor compounds.
Keywords: avocado